Risk Factors of High Grade Squamous Intraepithelial Lesions of Cervix in HIV Infected Women at Khon Kaen Hospital - Krittiya Somaketarin; Thumwadee Tangsiriwatthana; Veeraphol Srinil (The Royal Thai College of Obstetricians and Gynaecologists, 2015)
Objective:To determine risk factors associated of high grade squamous intraepithelial lesion (HSIL) in HIV infected women. Material and Methods: Retrospective cohort study of 250 HIV infected women registered in colposcopy clinic at Khon Kaen Hospital between January 1st 2008 and January 1st 2014 who had high grade histology (HSIL) was conducted. Risk factors associated with HSIL histology were studied between HSIL and low grade squamous intraepithelial lesion (LSIL) plus normal histology group. Risk factors were analyzed by logistic regression and recurrence of HSIL was analyzed by survival analysis.Results: The colposcopic records of 250 HIV infected women were analyzed. Mean age was 36.0 ± 7.5 years, and the mean CD4 cell count was 391.0 ± 229.3 cell/μL. Age ≥ 35 years was only significant risk factor associated with HSIL histology in HIV infected women (RR 2.06, 95% CI = 1.17 - 3.63). There were 32 (29.4%) and 7 (5.0%) women in HSIL and LSIL group had recurrent of HSIL histology respectively. Median time to recurrence of HSIL group compared with LSIL group was 55.6 months versus 59.8 months (p < 0.05).Conclusion: Age ≥ 35 years was a risk factor of HSIL histology in HIV infected women. Higher recurrence of HSIL was found in HSIL group.